Maritime Paradiplomacy of the 15th-Century Malay Sultanate: An Inspirational Model for Contemporary Archipelagic Regional Autonomy in Indonesia - Bagus Subagja; Sariyatun Sariyatun; Deny Tri Ardianto (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
ndonesia, the world’s largest archipelagic state, faces complex maritime governance challenges stemming from a disconnect between its decentralized legal framework and its centralist administrative practices. Despite constitutional provisions allowing regional entities to engage in international cooperation, bureaucratic hurdles undermine the effectiveness of maritime paradiplomacy, particularly in regions such as the Riau Islands and North Maluku. This study aims to address this gap by examining the 15th-century Melaka Sultanate as a historical model of decentralized maritime diplomacy that can inspire modern policy innovations. Utilizing a qualitative historical-comparative method, the research juxtaposes Melaka’s port-based paradiplomatic mechanisms such as the empowered role of syahbandars and strategic diaspora networks with Indonesia’s current regulatory constraints. Primary data were sourced from historical manuscripts including Suma Oriental and Yingya Shenglan, while contemporary policies were analyzed through legal documents and regulatory simulations. The findings reveal that Melaka's distributed sovereignty, pragmatic neutrality, and cultural diplomacy through maritime networks facilitated effective transregional cooperation, in stark contrast to Indonesia's modern procedural stagnation. As a conclusion, the study proposes the revival of localized diplomatic authorities through